Expression, Characterization and Its Deinking Potential of a Thermostable Xylanase From Planomicrobium glaciei CHR43 - Liu, Zhaoxing; Shao, Tingting; Li, Yan; Wu, Bin; Jia, Honghua; Hao, Ning (Frontiers in Bioengineering and Biotechnology, 2021)
Genome mining is more and more widely used in identifying new enzymes from database. In the present study, we have mined a putative xylanases, Pg-Xyn (UPI0003DF1784), from Planomicrobium glaciei CHR43, a psychrotolerant strain, whose xylanase-encoding gene was identified via genome mining from Genbank. Sequence analysis and homology modeling showed that Pg-Xyn belongs to glycosyl hydrolase family 10. On the basis of heterologous expression in E. coli and biochemical characterization, we found Pg-Xyn was most active at pH 9.0 and 80 °C and exhibited good stability from pH 5.0 to 12.0 and below 90 °C. Pg-Xyn was slightly activated in the presence of Ca2+ and Mg2+, while it was strongly inhibited by Mn2+. The analysis of hydrolysis products showed that Pg-Xyn was an endo-β-1,4-xylanase. In addition, Pg-Xyn performed good deinking ability in a paper deinking test. In consideration of its unique properties, Pg-Xyn might be a promising candidate for application in the paper and pulp industries.